Experimental and numerical investigation of helicopter fuselage model with active flow control - De Gregorio, F.; Vitagliano, P.L. (My University, 2014)
Scope of the work was investigating both experimentally and numerically the flow characteristics in the wake region of a simplified helicopter fuselage model featuring a rear ramp. A dedicated wind tunnel test campaign was carried out, including surface pressure and flow field measurements. The possibility to decrease the pressure drag and to improve the aerodynamic performance was investigated using two types of active flow control (AFC) systems: a “steady jet” actuator and a “pulsed jet” actuator, blowing from three slots located near the edges of the loading ramp. Several AFC operating configurations were tested by changing the blowing coefficient at the three slots and the pulsed jet reduced frequency. Useful information and deeper understanding of the flow behavior was obtained for a future test campaign scheduled on larger scale in an industrial wind tunnel. The results indicated that one operating condition was definitely more efficient than the others. Threshold values were observed in the functioning of the AFC actuators. In parallel the aerodynamic behavior of the fuselage model have been investigated by CFD simulations, with the objective to demonstrate the capabilities and limitations of currently available unsteady flow solvers to reproduce the flow features and the wake modifications induced by flow control, and the perspective to design better flow control techniques and model shapes. The paper reports the experimental set-up, the steady and pulsed jet flow control systems, the CFD methodology, a selection of the gathered results, comparisons between experimental and numerical results and perspective of the futures activities.